Modest de novo Reactivation of Single HIV-1 Proviruses in Peripheral CD4+ T Cells by Romidepsin - Kjær, Kathrine; Leth, Steffen; Konrad, Christina V.; Gunst, Jesper D.; Nymann, Rasmus; Østergaard, Lars; Søgaard, Ole S.; Schleimann, Mariane H.; Tolstrup, Martin; Denton, Paul W. (Frontiers in Virology, 2021)
A cure for human immunodeficiency virus (HIV-1) is restricted by the continued presence of a latent reservoir of memory CD4+ T cells with proviruses integrated into their DNA despite suppressive antiretroviral therapy (ART). A predominant strategy currently pursued in HIV-1 cure-related research is the “kick and kill” approach, where latency reversal agents (LRAs) are used to reactivate transcription from integrated proviruses. The premise of this approach is that “kicking” latent virus out of hiding allows the host immune system to recognize and kill infected cells. Clinical trials investigating the efficacy of LRAs, such as romidepsin, have shown that these interventions do induce transient spikes in viral RNA in HIV-1-infected individuals. However, since these trials failed to significantly reduce viral reservoir size or significantly delay time to viral rebound during analytical treatment interruptions, it is questioned how much each individual latent provirus is actually “kicked” to produce viral transcripts and/or proteins by the LRA. Here, we developed sensitive and specific digital droplet PCR-based assays with single-provirus level resolution. Combining these assays allowed us to interrogate the level of viral RNA transcripts from single proviruses in individuals on suppressive ART with or without concomitant romidepsin treatment. Small numbers of proviruses in peripheral blood memory CD4+ T cells were triggered to become marginally transcriptionally active upon romidepsin treatment. These novel assays can be applied retrospectively and prospectively in HIV-1 cure-related clinical trials to gain crucial insights into LRA efficacy at the single provirus level.